Looking for Marco - Armstrong, Alan., 1939- (Random House, 2009)
When they lose touch with his father's Gobi Desert expedition, eleven-year-old Mark accompanies his mother to Venice, Italy, and there, while waiting for news of his father, learns about the legendary Marco Polo and his adventures in the Far East.